If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 3y = -6 Solving -4x + 3y = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -4x + 3y + -3y = -6 + -3y Combine like terms: 3y + -3y = 0 -4x + 0 = -6 + -3y -4x = -6 + -3y Divide each side by '-4'. x = 1.5 + 0.75y Simplifying x = 1.5 + 0.75y
| 8x+y-3x+9y= | | 5x-3=-6 | | -(4y+1)-(3y-7)=-1 | | 2x^2-9x-200= | | 6.44w-7.59=7.73-1.86w | | y(5y-4)+(81+y^2)=0 | | 2-1.1j=7.5 | | 4.2-7z=2.8 | | 8.72z+0.44=9.79z+3.43 | | 6(3x-2)=3(6x+8) | | 0.2-3=-8.6 | | x^2+9x-96=0 | | 0.16+8.68w=-1.33-5.61w | | 27=7-2x | | 3y=x+12 | | 4+4z-1=8z+3-2z | | 7(3x-5)+4x+5=3(5x-6)+3x-5 | | -4n^2+6n-16=-15 | | 2k^2=27k-81 | | 0.5-0.25x=8 | | -4x+10=54 | | -1.97z+7.17=-6.91+3.55z | | X-.15x=36.24 | | X^2+-8x=-16 | | 28-4x=-12 | | 2k^2=-6k-4 | | x^2+10cosx=0 | | x^2+17x=-49 | | 2(4x+3)-3x=3(2x-1)+6 | | 2m+13m=120 | | 7r+8-3r=2(r+12)-6 | | x+1.5=1.2 |